Time-lapse processing of 2D seismic profiles with testing of static correction methods at the CO2 injection site Ketzin (Germany) - Bergmann, P.; Yang, C.; Lüth, S.; Juhlin, Christopher; Cosma, C. (2011)
The Ketzin project provides an experimental pilot test site for the geological storage of CO2. Seismic monitoring of the Ketzin site comprises 2D and 3D time-lapse experiments with baseline experiments in 2005. The first repeat 2D survey was acquired in 2009 after 22kt of CO2 had been injected into the Stuttgart Formation at approximately 630m depth. Main objectives of the 2D seismic surveys were the imaging of geological structures, detection of injected CO2, and comparison with the 3D surveys. Time-lapse processing highlighted the importance of detailed static corrections to account for travel time delays, which are attributed to different near-surface velocities during the survey periods. Compensation for these delays has been performed using both pre-stack static corrections and post-stack static corrections. The pre-stack method decomposes the travel time delays of baseline and repeat datasets in a surface consistent manner, while the latter cross-aligns baseline and repeat stacked sections along a reference horizon. Application of the static corrections improves the S/N ratio of the time-lapse sections significantly. Based on our results, it is recommended to apply a combination of both corrections when time-lapse processing faces considerable near-surface velocity changes. Processing of the datasets demonstrates that the decomposed solution of the pre-stack static corrections can be used for interpretation of changes in near-surface velocities. In particular, the long-wavelength part of the solution indicates an increase in soil moisture or a shallower groundwater table in the repeat survey. Comparison with the processing results of 2D and 3D surveys shows that both image the subsurface, but with local variations which are mainly associated to differences in the acquisition geometry and source types used. Interpretation of baseline and repeat stacks shows that no CO2 related time-lapse signature is observable where the 2D lines allow monitoring of the reservoir. This finding is consistent with the time-lapse results of the 3D surveys, which show an increase in reflection amplitude centered around the injection well. To further investigate any potential CO2 signature, an amplitude versus offset (AVO) analysis was performed. The time-lapse analysis of the AVO does not indicate the presence of CO2, as expected, but shows signs of a pressure response in the repeat data. © 2011 Elsevier B.V.